Model Tata Letak Kantor Terhadap Produktivitas Kerja Karyawan Pada Koperasi Serba Usaha Mitra Saudara - Heri Nugraha; Yassinta Purnama Sari; Muhammad Haris Fadhillah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This research aims to find out how much influence office layout has on the work productivity of employees of the Koperasi Serba Usaha (KSU) Mitra Saudara. The method used is a case study and the subjects are KSU Mitra Saudara employees. Meanwhile, the analysis technique uses simple linear regression to test the hypothesis of the influence of office layout on employee work productivity. The results of the research show that office layout has an effect on employee work productivity at KSU Mitra Saudara, namely 77.6%.